Resilience-based evaluation of urban drainage systems: The 'Safe & SuRe' Approach Paper 16 -Session 5: Emerging technology and asset management - Mugume, Seith N.; Butler, David (Research gate, 2016)
The need to develop more resilient urban drainage systems (UDSs) is now widely recognised as key to maintaining acceptable flood protection service levels in cities in view of emerging climate-related, urbanisation and ageing infrastructure threats. In order to effectively operationalise resilience in urban flood management, new quantitative evaluation approaches that consider ‘all possible threats’ including existing network capacity and asset failures such as sewer collapse, blockage or equipment malfunction are required. This paper presents the Safe & SuRe approach that seeks to ensure that UDSs are designed or retrofitted not only for safe (reliable) provision of services during normal conditions but also to be more resilient to extreme loading conditions. Specifically, the paper describes the developed Safe & SuRe framework and presents a summary of results obtained by applying the middle state-based Global Resilience Analysis (GRA) method to systematically evaluate: (i) the effect of a wide range of functional (hydraulic) and structural (sewer) failures and on the ability of an existing UDS in Kampala, Uganda to minimise the resulting magnitude and duration of flooding and (ii) investigate the effectiveness of a set of promising adaptation strategies on improvement of its resilience to flooding. Study results indicate that occurrence sewer failures leads to significant loss of functionality of the existing UDS (and hence its level of resilience to flooding) that is comparable to the effect of extreme rainfall. The results further indicate that when compared to centralised storage and improved asset management, the distributed storage strategy is more effective and leads to a reduction in total flood volume and mean flood duration of up to 34% and 24% respectively even when the UDS structure is significantly degraded. The presented GRA method provides a computationally efficient approach that is suitable for evaluating resilience in large urban drainage networks without prior knowledge of threat (extreme rainfall or sewer failure) occurrence probabilities.
Keywords: extremes; functional failure; reliability; resilience; structural failure